2012
DOI: 10.1111/j.1365-2648.2012.06046.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual framework of acute care nurse practitioner role enactment, boundary work, and perceptions of team effectiveness

Abstract: The new framework can guide decision-making and research related to the structures, processes, and outcomes of nurse practitioner roles in healthcare teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 76 publications
0
43
0
Order By: Relevance
“…We could not come to a consensus on adopting or adapting one of these models for the framework. Each model had strengths, but in relation to the framework's objectives were limited by their focus on a specific role (Kilpatrick, Lavoie‐Tremblay, Lamothe, Ritchie, & Doran, ; Sidani & Irvine, ), aspect of care (Mitchell, Ferketich, Jennings, & American Academy of Nursing Expert Panel on Quality Health Care, ), or quality improvement (National Council for Nursing and Midwifery, ); and the lack of complexity (Byers & Brunell, ).…”
Section: Resultsmentioning
confidence: 99%
“…We could not come to a consensus on adopting or adapting one of these models for the framework. Each model had strengths, but in relation to the framework's objectives were limited by their focus on a specific role (Kilpatrick, Lavoie‐Tremblay, Lamothe, Ritchie, & Doran, ; Sidani & Irvine, ), aspect of care (Mitchell, Ferketich, Jennings, & American Academy of Nursing Expert Panel on Quality Health Care, ), or quality improvement (National Council for Nursing and Midwifery, ); and the lack of complexity (Byers & Brunell, ).…”
Section: Resultsmentioning
confidence: 99%
“…This study provides in‐depth descriptions from the perspective of providers and adds to our understanding of the multilevel influences and the interrelated nature of processes within teams (Sidani & Doran , Kilpatrick et al . ,b). The study findings support the processes identified by Kilpatrick et al .…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by Yin (), a conceptual framework was developed to support all the phases of the case study (Kilpatrick et al . ). The digital recordings of the interviews were transcribed and read several times ‘to obtain a sense of the whole’ (Graneheim & Lundman p. 108).…”
Section: Methodsmentioning
confidence: 97%
“…We acknowledge that some scholars conceptualize ''enactment'' as a term relating to the mode in which various role components are carried out. 12 …”
Section: Ré Sumémentioning
confidence: 99%